PROSES PERUBAHAN PENGGUNAAN LAHAN SAWAH DI KOTA BUKITTINGGI - Alifah Tahsya; Ahyuni Ahyuni (JURNAL BUANA, 2026)
This study aims to determine 1) Changes in the use of paddy fields in the City of Bukittinggi from 2012 – 2021, 2) The process of changes in the use of paddy fields in the City of Bukittinggi in 2012 – 2021. The research method used in this study is a mixed method. Based on the research results, the research results obtained 1) From 2012 to 2021 paddy fields that have turned into settlements amounted to 25.57 ha, 2) The process of changing the use of paddy fields in the City of Bukittinggi starts with obtaining land certificates from the BPN and then proceeding with leveling the land, land preparation and building construction. Changes in paddy fields in the City of Bukittinggi occurred due to three factors, namely the existence of educational facilities would trigger the change of paddy fields into supporting facilities for educational areas, an increase in trading businesses where this increase would trigger a change in paddy fields into complementary businesses, and an increase in the road network, namely road construction would triggering the surrounding paddy fields to turn into business buildings and settlements.